2013
DOI: 10.1007/s13197-013-1045-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the addition of natural antioxidant from mate leaves (Ilex paraguariensis St. Hill) on the chemical, microbiological and sensory characteristics of different formulations of Prato cheese

Abstract: The objective of this work is to evaluate the effects of the addition of dried extract from mate leaves and mesophilic cultures (Lactococcus lactis ssp. lactis and cremoris) on the chemical, microbiological and sensory characteristics of Prato cheese. The Prato cheese presented high moisture contents (49 to 53 %) and mean pH values of 5.15 for all tested formulations. The addition of mate leaves extract in the product did not influence the growth of the microbial cultures. During the maturation time, all formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…This increase can be due to the consumption of the residual lactose by the cultures, and greater retention of residual lactose in the product, since the process does not include the curd washing step. Faion et al (2013) observed an increased acidity in the Prato cheese, whose manufacturing process did not include curd washing, as in this study. The authors attributed this increase to the degradation of residual lactose by lactic cultures.…”
Section: Cheese Characterisation During Ripeningsupporting
confidence: 71%
See 2 more Smart Citations
“…This increase can be due to the consumption of the residual lactose by the cultures, and greater retention of residual lactose in the product, since the process does not include the curd washing step. Faion et al (2013) observed an increased acidity in the Prato cheese, whose manufacturing process did not include curd washing, as in this study. The authors attributed this increase to the degradation of residual lactose by lactic cultures.…”
Section: Cheese Characterisation During Ripeningsupporting
confidence: 71%
“…The genetic variants b-CN A 1 and A 2 suffered poor hydrolysis during storage with the formation of small peaks of g-CN, and the formation of the peak g 2 -CN in the first 7 days of storage. After this period, the fraction b-CN remained almost intact throughout storage, suggesting a low activity of plasmin (Fox, Guinee, Cogan, & McSweeney, 2000) and low specificity of bacterial peptidases on the fraction of b-CN (Ong, Henriksson, & Shah, 2007).…”
Section: Cheese Characterisation During Ripeningmentioning
confidence: 99%
See 1 more Smart Citation
“…pH value of White cheeses made with the addition of 0.5, 1, 1.5 and 2% pollen bee were significantly lower than the control treatment at zero time of repining period (P< 0.05 (Figure 3). pH values increased after 45 days of repining period, which might be attributed to the fermentation of lactose by starter cultures (Faion et al 2015). Najgebauer-Lejko et al, (2011) who reported that the tea polyphenols were of a positive effect on yoghurt acidity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the resultant cheeses with 1.5 and 2 % pollen bee characterized with the lowest scores for odour appearance, body and texture and flavour, while the addition of 0.5 and 1% bee pollen were of the highest scores for sensory properties of White cheeses. Faion et al, (2015) found that addition 0.2 wt. % of mate extract affected flavour, texture and acceptance of Prato cheese , which was of a bitter flavour after 45 days.…”
Section: Resultsmentioning
confidence: 99%